Sustainable construction through eco-efficient ultra-high performance concrete - Ferdosian, I. (2016)
An innovative type of steel-fibre reinforced ultra-high performance concrete (UHPC), including its constituent materials and its mixing procedure, is reviewed in this paper. Furthermore, an energy-efficient curing method for developing precast UHPC members is presented as the main goal of the current study. It was found that just with 24 hours of curing in tempered water or steam with 67Â°C, 95% of 28-day compressive strength in normal curing method, 145 MPa, could be achieved which would be of great interest for prefabrication industry regarding their energy consumption. It also would be beneficial for any project in which early load-bearing capacity is expected. Self-compactness, compressive strength higher than 150 MPa, improved durability and finally low curing energy in precasting phase of the material all offer variety of slim interior and exterior architectural and structural applications even in high-rise structures and aggressive environments where higher strength, ductility and durability is required.